Somalia’s Tripartite Federalism Oxymoron: Building Democratic Institutions and Political Legitimacy in a Fragile Federation - Hashi, Mohamed Bile; Hock, Oo Yu (2024)
The study aims to explore the inherent tensions and complexities of pursuing democratic institution building and developing political legitimacy within the context of Somalia’s fragile and seemingly contradictory tripartite federal system. In order to obtain the data needed to meet the study’s objective, twenty-five (25) key informants were interviewed using a qualitative research approach. Key informants’ interview responses show that the enervating political legitimacy both undermines institution building and contributes to the ongoing conflict in Somalia, thus making the prospect of restoring order a challenging undertaking, and the instability of Somalia’s federalism conspicuously prominent! Legitimacy is a fundamental principle of politics that is premised upon the right to rule or govern. However, in Somalia’s context, the right to govern and the political obligation arising therefrom involve the culture-bound informal and formal consent, norms and laws of Islam that continue to influence the vicissitudes of political legitimacy and institution building needed to stabilize Somalia’s federalism. In addition, the stability of Somalia’s federalism requires effective institution building with political legitimacy that enables a strong government structure that promotes accountability and divert the clan-based power struggle to inclusive state. The results from this study endorse the argument that political legitimacy requires fair elections based on indigenous principles and open to all parties of the community, a legitimate and publicly ratified constitution, parties based on ideology, a civic state, honest leadership that wants to build the country, a distinct separation and distribution of power among institutions, and freedom of speech within legal bounds.